2019
DOI: 10.21037/tcr.2019.04.21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high expression profiles of miR-31-5p and its vital role in lung squamous cell carcinoma: a survey based on qRT-PCR and bioinformatics analysis

Abstract: Background The function of miR-31-5p in lung squamous cell carcinoma (LUSC) remains unclear, therefore, a systematic study was performed for the clinical significance and molecular mechanism of miR-31-5p in LUSC. Methods Quantitative real-time reverse transcription PCR (qRT-PCR) was utilized to test the expression level of miR-31-5p in 88 LUSC tissue samples and their matching normal tissues. Data from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Lung cancer is by far the largest contributor to cancer death with a 5-year relative survival rate of only 19%, and lung squamous cell carcinoma (LUSC) is the second common form of lung cancer (1,2). The current treatment for LUSC patients diagnosed at an early stage is surgical resection followed by the administration of adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is by far the largest contributor to cancer death with a 5-year relative survival rate of only 19%, and lung squamous cell carcinoma (LUSC) is the second common form of lung cancer (1,2). The current treatment for LUSC patients diagnosed at an early stage is surgical resection followed by the administration of adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Its suppressive function has been shown to be markedly diminished in hepatocellular (HCC), renal carcinoma, and CNS malignancies, while expression of its target genes is enhanced resulting in increased cell division (8,9). Furthermore, miR-31 expression was significantly increased in pancreatic, colorectal, and lung cancer, and resulted in suppression of the genes regulating significant cellular activities (10,11). A few studies have suggested that miR-31 is a vital controller of BC metastasis (8,12).…”
mentioning
confidence: 99%